(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2015)
Background: Endoscopic third ventriculostomy (ETV) is the process of intra cranial CSF diversion to relieve the pressure inside the ventricles. This allows the cerebrospinal fluid to flow directly to the basal cisterns, thereby shortcutting any obstruction. It is used as an alternative to a cerebral shunt surgery. Objectives: To observe the Endoscopic third ventriculostomy (ETV) with causal factors and outcome. Methodology: The study was conducted in the Department of Neurosurgery in National Institute of Neurosciences (NINS) during the period from June, 2013 to August, 2014. All the study subjects included in the study were selected for endoscopic third ventriculostomy (ETV) following clinical and radiological diagnosis of hydrocephalus or raised ICP irrespective of age, sex and causal factors. The patients were followed post operatively to follow the outcome. Result: ETV was performed among 38 males and 35 females with a mean age of 24.67 years. Three major causal factors for ETV were aqueductal stenosis, posterior fossa SOL and CP angle tumour observed in 25 (34.3%), 22(30.2%), 11(15.1%) cases respectively. The successful ETV was done in 49 (67.1%) patients varied widely by diagnosis and patient age. Other 32.9% had suffered from several complications like local CSF drainage, local infection, meningitis and subarachnoid haemorrhage and treated conservatively. Conclusion: Endoscopic third ventriculostomy (ETV) is a safe and successful procedure in the management obstructive hydrocephalus. J. Natl Inst. Neurosci Bangladesh 2015;1(1):5-7